The effects of positive electronic word-of-mouth on purchase intention of Malaysian consumers - Al Masud, Abdullah; Haque, A. K. M. Ahasanul (Mac Arts & Communication, 2023)
The main objective of this research is to investigate the effects of positive electronic word-of-mouth towards online purchase intention of customers in Malaysia. The aggressive promotional activities in social media platforms by the product marketers put the customers in a dilemma while purchasing products online. A quantitative research design has been adopted to conduct this study by investigating 428 valid responses collected from survey. The respondents were selected conveniently from Malaysia who visit online shopping platforms like Lazada, Shopee, Amazon and 11 Street. IBM SPSS (version 25) and SmartPLS (version 4) statistical programs have been used to analyse the data and validate the proposed hypotheses. This study finds that electronic word-of-mouth is a significant predictor for customers’ online purchase intension. The outcome from this research has contributed to new practical insights. The study concludes that online product marketers need to strategies their promotions by enabling favourable electronic word-of-mouth from contented customers via social media channels and dedicated customer review sections through their platforms.